A Green Heterogeneous Catalyst Production and Characterization for Biodiesel Production using RSM and ANN Approach - Aditya Kolakoti; Muji Setiyo; Muhammad Latifur Rochman (International Journal of Renewable Energy Development, 2022)
In this work, naturally available moringa oleifera leaves (also known as horseradish trees or drumstick trees) are chosen as a heterogeneous catalyst in the transesterification for biodiesel production from palm oil. The dry moringa oleifera leaves are calcinated at 700 °C for 3 hours to improve their adsorbing property. The calcinated catalyst characterization analysis from XRD and EDX highlights the presence of calcium, potassium, and other elements. Response surface method (RSM) optimization and artificial neural network (ANN) modeling were carried out to elucidate the interaction effect of significant process variables on biodiesel yield. The results show that a maximum biodiesel yield of 92.82% was achieved at optimum conditions of catalyst usage (9 wt.%), molar ratio, methanol to triglyceride (7:1), temperature (50 °C) and reaction time (120 min). The catalyst usage (wt.%) was identified as a significant process variable, followed by the molar ratio. Furthermore, the biodiesel’s significant fuel properties in terms of thermal, physical, chemical, and elemental match the established standards of ASTM. Finally, when the catalyst was reused for five cycles, more than 50% of the biodiesel yield was achieved.